2007
DOI: 10.1111/j.1525-1438.2007.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in Indian women with cervical intraepithelial neoplasia and cancer cervix

Abstract: Cervical cancer develops from the preneoplastic cervical intraepithelial neoplasia (CIN). Host factors are critical in regulating tumor growth and cytokines, which modulate immunologic control may be of particular importance. The objective of this study was to assess the production of cytokines by peripheral blood mononuclear cells (PBMCs) in Indian women with cancer cervix and CIN. Sixty patients with cancer cervix (including all FIGO stage I-IV), 35 patients with CIN, and 30 healthy controls were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
2
47
1
5
Order By: Relevance
“…The upregulated secretion of IL-10 may inhibit immune response against HPV infection in early cervical lesions. Reports have shown that higher IL-10 could be detected in plasma of patients with CIN III and with carcinoma than in patients with CIN I and CIN II (11)(12)(13). Moreover, patients suffering from cervical cancer show higher IL-10 expression in HPV16-positive tumors than in HPV16-negative tumors, which again indicates an association between IL-10 and the carcinogenesis of HPV-associated cancer (14).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The upregulated secretion of IL-10 may inhibit immune response against HPV infection in early cervical lesions. Reports have shown that higher IL-10 could be detected in plasma of patients with CIN III and with carcinoma than in patients with CIN I and CIN II (11)(12)(13). Moreover, patients suffering from cervical cancer show higher IL-10 expression in HPV16-positive tumors than in HPV16-negative tumors, which again indicates an association between IL-10 and the carcinogenesis of HPV-associated cancer (14).…”
Section: Introductionmentioning
confidence: 61%
“…HPV infection is a major etiologic factor in cervical carcinogenesis. IL-10 mRNA levels in cervical intraepithelial neoplasia (CIN) were significantly higher compared with normal cervical tissues (11)(12)(13). The upregulated secretion of IL-10 may inhibit immune response against HPV infection in early cervical lesions.…”
Section: Introductionmentioning
confidence: 95%
“…An increased number of IL-10-positive cells was detected in the cervix of patients with cervical intraepithelial neoplasia (CIN), associated with the grades of dysplasia (15). Furthermore, an increase in the levels of IL-10 was observed in cervical cancer and CIN grade III patients, compared to those with early CIN grades and healthy controls (16). The genotype predisposing to the production of high levels of IL-10 is more commonly observed in cervical cancer patients, compared to healthy women (17).…”
Section: Introductionmentioning
confidence: 88%
“…Many of the authors have evaluated immune markers that were locally secreted in the cervix, tissue-based immune markers or immune response by patient-derived peripheral blood mononuclear cells (PBMCs) [27][28][29][30]. However, data concerning infection-related immune response in either plasma or serum is limited.…”
Section: Discussionmentioning
confidence: 99%